1997
DOI: 10.1002/srin.199700580
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation of titanium nitride in low-alloyed steel during cooling and deformation

Abstract: The precipitation of titanium nitride in undeformed solid carbon-manganese steel has been investigated by means of metallography and electron microscopy at in-situ melted samples the cooling of which was interrupted at different temperatures for a defined time. The deformation-induced precipitation of titanium nitride was studied on samples which were in-situ melted in a torsion plastometer, deformed after solidification, re-deformed after a holding time, and quenched. Additionally, 50 mm slabs were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…13) As the solubility of TiN is very low in Fe the full stabilization of N is expected in the IFHS steels. [14][15][16] The amount of Ti (in wt%) required to tie up with N is 3.42 times of the N present in the steels. 6,17) In IFHS steels N is generally kept below 40 ppm and thus maximum Ti required to tie up with N is 0.014 wt%.…”
Section: Precipitates In Ifhs Steelsmentioning
confidence: 99%
“…13) As the solubility of TiN is very low in Fe the full stabilization of N is expected in the IFHS steels. [14][15][16] The amount of Ti (in wt%) required to tie up with N is 3.42 times of the N present in the steels. 6,17) In IFHS steels N is generally kept below 40 ppm and thus maximum Ti required to tie up with N is 0.014 wt%.…”
Section: Precipitates In Ifhs Steelsmentioning
confidence: 99%
“…The solid lines in the figure are on the basis that bulk concentrations are equal to the initial concentrations since a certain supersaturation is necessary for precipitate nucleation. For instance, Kunze et al 17) reported that TiN particles only formed in the regions where the supersaturation was higher than 15 fold. The dash lines are also for equilibrium conditions with no concentration gradients in the matrix and precipitates, but on the assumption that (NbTi) (CN) precipitates in equilibrium at 1 150°C are removed from the system.…”
Section: Modeling the Precipitation In Steelsmentioning
confidence: 99%
“…The above compositional variation predicted by the thermodynamic analysis is a consequence of the continuous mutual solubility of the carbides and nitrides formed by Ti, Nb and V and of the decreasing solubility of the different carbides and nitrides with temperature in the giron. [1][2][3][4][5] …”
Section: Resultsmentioning
confidence: 99%
“…A proper design of the carbonitride precipitation sequence through control of composition, solidification and cooling rate is therefore of great importance and it was the subject of a large number of research works in the last decades. [1][2][3][4][5][6][7] During recent years, particular attention was dedicated to optimisation of solidification conditions and avoidance of transversal and edge cracking, especially during continuous casting. From hot tensile testing and from industrial practice on microalloyed steel, it was established that a loss of ductility is often encountered at temperatures approximately ranging from 750 to 950°C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation